2013
DOI: 10.1371/journal.pntd.0002117
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival MicroRNA Expression in Inflammatory Trachomatous Scarring

Abstract: PurposeTrachoma is a fibrotic disease of the conjunctiva initiated by Chlamydia trachomatis infection. This blinding disease affects over 40 million people worldwide yet the mechanisms underlying its pathogenesis remain poorly understood. We have investigated host microRNA (miR) expression in health (N) and disease (conjunctival scarring with (TSI) and without (TS) inflammation) to determine if these epigenetic differences are associated with pathology.MethodsWe collected two independent samples of human conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…However, it would be interesting to determine if these miRNA responses persist in Nigg A -infected mice at later time points. Moreover, upregulation of profibrotic miR-142-3p and miRNA 147 were also observed with Nigg V infection, consistent with the inflammatory C. trachomatis scarring model (28). Nigg V infection results in a higher bacterial load; thus, it is possible that increased inflammatory responses and miRNA expression are due to a higher replicative capacity of the chlamydiae.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, it would be interesting to determine if these miRNA responses persist in Nigg A -infected mice at later time points. Moreover, upregulation of profibrotic miR-142-3p and miRNA 147 were also observed with Nigg V infection, consistent with the inflammatory C. trachomatis scarring model (28). Nigg V infection results in a higher bacterial load; thus, it is possible that increased inflammatory responses and miRNA expression are due to a higher replicative capacity of the chlamydiae.…”
Section: Discussionsupporting
confidence: 74%
“…miRNAs and Chlamydial Pathogenesis Infection and Immunity fibrosis and epithelial cell differentiation in human samples of chlamydial conjunctival inflammatory scarring (28). The study indicated that significant changes in miRNA expression are associated with the late-stage disease process.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…16 In humans, microRNAs have been implicated in various diseases, 11,[22][23][24] including neovascularization 25 and fibrosis. However, the involvement of microRNAs in ocular surface fibrosis have been limited to descriptive studies of microRNA levels in diseases, 26 or induction by laser, 27 exogenous growth factor 28,29 or immunosuppressive drugs 30,31 in non-disease derived cultured ocular surface fibroblasts.…”
Section: Introductionmentioning
confidence: 99%